2008
DOI: 10.1016/j.jviromet.2008.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Cloning the complete guinea pig cytomegalovirus genome as an infectious bacterial artificial chromosome with excisable origin of replication

Abstract: Congenital human cytomegalovirus infections are the major infectious cause of birth defects in the United States. How this virus crosses the placenta and causes fetal disease is poorly understood. Guinea pig cytomegalovirus (GPCMV) is a related virus that provides an important model for studying cytomegaloviral congenital transmission and pathogenesis. In order to facilitate genetic analysis of GPCMV, the 232kb GPCMV genome was cloned as an infectious bacterial artificial chromosome (BAC). The BAC vector seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
94
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 39 publications
(95 citation statements)
references
References 29 publications
1
94
0
Order By: Relevance
“…Cell culture propagation of virus was carried out in guinea pig lung (GPL) fibroblast cells (ATCC CCL158) maintained in F-12 medium supplemented with 10% fetal calf serum (FCS; Fisher Scientific), 10,000 IU/liter penicillin, 10 mg/liter streptomycin (Gibco-BRL), and 0.075% NaHCO 3 (Gibco-BRL) or as described previously (33). Growth curves and viral titers were determined as described previously (39).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell culture propagation of virus was carried out in guinea pig lung (GPL) fibroblast cells (ATCC CCL158) maintained in F-12 medium supplemented with 10% fetal calf serum (FCS; Fisher Scientific), 10,000 IU/liter penicillin, 10 mg/liter streptomycin (Gibco-BRL), and 0.075% NaHCO 3 (Gibco-BRL) or as described previously (33). Growth curves and viral titers were determined as described previously (39).…”
Section: Methodsmentioning
confidence: 99%
“…BAC construct N13R10 contains the complete GPCMV strain 22122 genome, while the BAC N2 contains a 17.9-kb deletion (39). BAC N2 with a targeted deletion of gp145 (N2-⌬145) and N13R10 with a targeted deletion of gp145 (N13R10-⌬145 or ⌬145) were constructed using a linear recombination approach to result in the substitution of a kanamycin resistance cassette (Kn) for nucleotides 224206 to 226104 (GenBank accession number KM384022 [25]) comprising the gp145 open reading frame (Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…BAC N13R10 contains the complete GPCMV strain 22122 genome (9), with a deletion that disrupts open reading frames (ORFs) GP129 and GP130. BAC N13R10-r129 was constructed using a two-step galactokinase-mediated recombineering approach (19).…”
Section: Virus and Cells Cell Culture Propagation Of Virus Was Carrimentioning
confidence: 99%
“…Prior studies reported the successful cloning of the genome of a tissue culture-attenuated variant of GPCMV strain 22122 as a bacterial artificial chromosome (BAC) designated N13R10 (9). Although virus derived from N13R10 grows like wild-type GPCMV in cell culture, it was highly attenuated in vivo compared to pathogenic salivary gland (SG)-adapted virus.…”
mentioning
confidence: 99%